Computed Tomographic Assessment of Liver in Dog Cadaver - Sohoni, Kaveri S.; Shankhapal, Vinod D.; Gaikwad, Santosh A.; Yadav, Girish U.; Lambate, Sanjay B. (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was conducted to perform a detailed anatomical and imaging-based evaluation of liver in eight embalmed non-descript adult male dog cadavers. Helical non-contrast computed tomographic (CT) examination enabled cross-sectional visualization of liver in transverse, sagittal and dorsal planes and helped determine its spatial relationships and topographical position according to thoracic (T) and lumbar (L) vertebrae. The dog cadavers were procured and embalmed using Thiel’s solution. Non-contrast helical CT imaging was performed using a 128-slice computed tomographic scanner with slice thickness of 0.6 mm, and reconstruction interval of 0.3 mm using soft tissue window settings (window width 350 HU; window level 40 HU). In CT examination, liver appeared as a homogeneous soft tissue structure occupying the cranial abdominal cavity, extending from eighth thoracic (T8) to first lumbar (L1) vertebral levels. The hepatic parenchyma appeared to be continuous with the diaphragm. The mean attenuation value of liver recorded in the present study was 68.68 ± 5.48 HU. Minor alteration in the tissue density of liver (54.2-89.0 HU) was observed, which may be due to embalming of dog cadaver. The liver was hyperattenuating to the muscle and hypoattenuating to the bony structures of the ribs, vertebrae or sternum. The liver was hyperattenuating than the falciform ligament, mesentery and the perirenal fat.
Keywords: Computed tomography; Dog; Liver